Pengaruh Brand Ambassador dan Brand Image terhadap Keputusan Pembelian Skincare Benings - Sinulingga, Tiara Ramadhanti Wijaya; Meutia, Riza Fanny; Royani, Ida (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Outer beauty is physical beauty, the appearance that is visible to our five senses (Indriya, 2010:4). Outer beauty, in Syata (2012:58) outer beauty such as, white skin, good appearance, clean and a face that is more immediately prominent and visible. Beauty is something that is identical to women, where beauty itself is interpreted as a beauty and has an attraction. Data from all visitors to the Benings Clinic from August 2023 to October 2024 totaling 1,876 people. The sample is part of the number and characteristics possessed by the population. And the determination of the sampling technique used is sample random sampling, which is a sampling technique from population members that is carried out randomly without considering the strata in the population. Simple Random Sampling requirements from simple random sampling techniques: 1) This technique is used if the population elements are homogeneous, so that any element selected as a sample can represent the population. 2) It is done if the research analysis tends to be descriptive and general. And the number of samples is 95 people. From the research results, it is known that the calculated F value (18.629) is greater than the F table (3.09) and sig 0.000 0.05. This means that simultaneously brand ambassador (X1) has a positive and significant effect on purchasing decisions (Y). and brand image (X2) simultaneously has a negative effect on purchasing decisions (Y).